Environmental education for sustainability and its contribution to holistic learning at the Faculty of Architecture, Urbanism and Arts, National University of Engineering, Lima, Peru - Chilet Cama, Shirley Emperatriz (2021)
The objective of this study is to explain how environmental education for sustainability is important in student academic training for learning with a holistic vision at the Faculty of Architecture, Urbanism and Arts of the National University of Engineering in Lima. The basic research had a quantitative, causal correlational approach with a non-experimental design. The population consisted of 80 teachers and 100 students. The instrument applied was the questionnaire. It is evidenced that teachers, on a smaller scale, incorporate environmental education in their different subjects with attitudinal and axiological contents that contribute to the formation of values and attitudes of coexistence; but they do consider that environmental education is important for sustainability with a holistic vision.